2014
DOI: 10.1016/j.fct.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis identifies differentially expressed proteins after red propolis treatment in Hep-2 cells

Abstract: Here we investigated alterations in the protein profile of Hep-2 treated with red propolis using two-dimensional electrophoresis associated to mass spectrometry and apoptotic rates of cells treated with and without red propolis extracts through TUNEL and Annexin-V assays. A total of 325 spots were manually excised from the two-dimensional gel electrophoresis and 177 proteins were identified using LC-MS-MS. Among all proteins identified that presented differential expression, most were down-regulated in presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Others studies indicated that red propolis induces apoptosis on human tumour cells [ 2 , 12 ] that might be the mechanism behind the high index of cell inhibition induced by EEP at a concentration of 50 μg/mL showed in this study. Similar effect was also demonstrated by Begnini et al [ 22 ] that found the ethanolic extract of red propolis at concentrations of 50 and 100 μg/mL induced high levels of apoptosis in bladder carcinoma cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Others studies indicated that red propolis induces apoptosis on human tumour cells [ 2 , 12 ] that might be the mechanism behind the high index of cell inhibition induced by EEP at a concentration of 50 μg/mL showed in this study. Similar effect was also demonstrated by Begnini et al [ 22 ] that found the ethanolic extract of red propolis at concentrations of 50 and 100 μg/mL induced high levels of apoptosis in bladder carcinoma cells.…”
Section: Discussionsupporting
confidence: 57%
“…Propolis has been known since centuries for its healing properties but recently it has captured the attention of scientists due to its wide spectrum activities that can be used in the complementary and alternative medicine [ 6 8 ]. Consistently, the number of studies conducted with this substance has exhibited a significant increase in countries without the traditional use of natural medicine [ 2 , 9 – 12 ].…”
Section: Introductionmentioning
confidence: 88%
“…The best anti-proliferative effect showed by the red propolis extract, when compared to other samples of propolis may depend on its differentiated composition, for example, the presence of formononetin, the main isoflavones found in this type of propolis [ 123 124 ]. Recently, a polyisoprenylated benzophenone (xanthochymol) was also identified in the red propolis [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis was another major cause for Chinese propolis and CAPE to inhibit LPS-stimulated MDA-MB-231 cells survival. We and other researchers all reported that propolis could induce cancer cells apoptosis [ 6 , 31 ]. Here we also found that Chinese propolis and CAPE activated caspase 3- the executor of apoptosis in LPS-stimulated breast cancer cells, which might be induced by activating autophagy and depressing TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%